Planetarium Di Pekanbaru Dengan Pendekatan Arsitektur Futuristik - Siti Hajar Alwin; Mira Dharma Susilawaty; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Planetarium as a medium of learning and recreation on the science of astronomy can be displayed in the form of simulation demonstration/performances of celestial bodies. Seeing the highdevelopment of knowledge, Science, and Technology Astronomy, Pekanbaru as a developing city has a vision as a Smart City certainly demands to develop human resources in the field of Astronomy. Astronomy induced the need for container that can accommodate the learning and recreation needs with identical impression of the Planetarium. A Futuristic Architectural approach will be implemented in the building’s design that will expressing a creatiy and innovative display forms. Based on data collection, literature study, comparative study, and empirical study, they can be concluded the concept of Solar System able to make the Planetarium as the core design that is surrounded by supporting activities. By applying special materials on façade with future-oriented can be displayed at the design of this Planetarium.Keywords: Planetarium, Astronomy, Futuristic Architecture.